Синдром пьяного сердца - Приставкин Анатолий Игнатьевич (2010)
Экземпляры: ф.6 (20190830) / Инвентарный номер: 3264zzz / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 77 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-44